Breech at the Border: An Atypical Case of Invasive Haemophilus influenzae in a Patient on a Novel Immunotherapeutic. (26th June 2018) - Howard-Anderson, Jessica; Satola, Sarah W; Collins, Matthew H
Abstract: Haemophilus influenza e rarely causes pyogenic infections in the female genital tract, and even less commonly does this lead to systemic infections. Novel monoclonal antibody therapies targeting interleukin-17 may impair mucosal immunity, but increased risk for H. influenza e infections has not been documented. Here, we describe a case of H. influenza e bacteremia associated with pyosalpinx and hypothesize that immunomodulatory treatment for psoriasis predisposed our patient to this infection.